Tailoring Biodegradability of Poly(Butylene Succinate)/Poly(Lactic Acid) Blends With a Deep Eutectic Solvent - Delamarche, Emma; Mattlet, Agnès; Livi, Sébastien; Gérard, Jean-François; Bayard, Rémy; Massardier, Valérie (Frontiers in Materials, 2020)
Biodegradable polymers concern an important topic for innovation in materials, as they are supposed to contribute to the reduction in the amount of waste materials, which lead to microplastics with similar properties as conventional polymer materials. Poly(butylene succinate) and poly(lactic acid) blends are polymers with interesting properties offering possible alternatives to some conventional petrochemical-sourced polymers. Some of the physical properties of such blends can be tailored from the addition of small amounts of deep eutectic solvents (DESs) that can act as compatibilizers, i.e., interfacial agents between poly(butylene succinate) (PBS) and poly(lactic acid) (PLA). In our study, materials formulated with a DES having a coarse morphology according to the dispersed particle sizes display thermal and mechanical properties rather close to the non-compatibilized PBS/PLA blends but a higher ability to biodegrade. In comparison with PBS/PLA blend, biodegradation experiments show that PBS/PLA/DES blend exhibits higher weight losses and faster fragmentation under conventional conditions. A significant decrease in PLA melting temperature under composting conditions, i.e., at 58°C, is observed indicating that PLA phase is the component mainly concerned. As a conclusion, this work demonstrates that morphologies as well as the biodegradability process can be tailored by adding a small amount of a DES in such biosourced polymer blends. Indeed, designing polymer materials, for which degradation processes are targeted in the dispersed phase, i.e., in multiple locations of the material, can be an efficient route to “predegrade” phases in a polymer matrix to accelerate macroscopic biodegradation.